A novel aqueous route for separating aluminum and plastic recovery in multilayer packaging waste for sustainable recycling - Nguyen, Thi Thanh Truc; Nguyen, Thi Lan Binh; Le, Hung Anh; Vu, Dinh Khang (Hue University Journal of Science: Natural Science, 2025)
Multilayer packaging, such as blister packs and milk cartons, poses significant recycling challenges due to the strong interlayer adhesion. This study investigates the chemical separation of aluminum and plastic by using aqueous ammonia-based solutions. For pharmaceutical blister packs, an NH₃/NH₄Cl/H₂O solution was applied. Aluminum recovery was determined through titration of dissolved Al³⁺ and gravimetric analysis of residual foil; PVC recovery was measured with gravimetric methods. Under optimal conditions (5 M NH₃, 2.5 M NH₄Cl, 1:25 g/mL ratio, 60-minute immersion at 70 °C), the process achieved complete separation, yielding 10.7% aluminum and 88.8% plastic by mass. For milk cartons, separation was carried out using only an NH₄OH/H₂O solution under the same temperature and ratio, but with 5 M NH₄OH and 30-minute immersion. The recovered fractions included 7.8% plastic, 63.7% paper, and 26.3% aluminum-plastic composite, while no separated aluminum foil was observed. A maximum recovery efficiency of 97.82% was achieved, indicating substantial, though incomplete, material separation. These results demonstrate that while ammonia-based chemical treatments enable nearly complete recovery from blister packs, separation from milk cartons is less effective because of stronger bonding between aluminum and plastic. Nonetheless, the method contributes to resource recovery and waste reduction, supporting circular-economy goals in multilayer packaging management.